2022
DOI: 10.1108/ijoem-08-2021-1274
|View full text |Cite
|
Sign up to set email alerts
|

Whether, how and why home country environments influence emerging market firm acquisition behavior

Abstract: PurposeAccording to the 2019 World Investment Report, recent events in deglobalization have made many countries, especially developed markets, resist inward foreign direct investment (FDI) as ceding control to foreign countries. At the same time, many emerging market firms (EMFs) have been increasing their acquisitions in developed markets. The authors elaborate three unconventional motives that justify such acquisitions, and test whether conditions in home countries related to these motives predict the pursui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 103 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…, 2021). However, Reddy et al. (2023) suggested an opposite dynamic where increased ownership is an outcome of home institutional quality enhancement that drives EMFs to seek deeper learning from CBMA targets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021). However, Reddy et al. (2023) suggested an opposite dynamic where increased ownership is an outcome of home institutional quality enhancement that drives EMFs to seek deeper learning from CBMA targets.…”
Section: Resultsmentioning
confidence: 99%
“…This forms their motivation for conducting CBMAs and increasing ownership (Chari and Acikgoz, 2016;Deng, 2009;Li et al, 2021). However, Reddy et al (2023) suggested an opposite dynamic where increased ownership is an outcome of home institutional quality enhancement that drives EMFs to seek deeper learning from CBMA targets. Underdeveloped home institutions also affect EMFs' risk preference in ownership sought, such that Latin American acquirers are less negatively affected by host country risk in their ownership, given their adaptability to home high-risk environments (Krug and Falaster, 2023).…”
Section: Home Country Factors In Cbmas Bymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature is less comprehensive in analyzing how companies are sensitive to institutional differences in home and host countries (De Beule & Zhang, 2022). Therefore, despite the reported importance of the institutional environment, it is necessary to analyze which institutional factors drive the internationalization of MNCs and how these factors influence the strategies adopted by these companies in the international market (Ferreira & Falcao, 2019;Elango & Pangarkar, 2021;Reddy et al, 2022;Zhu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally dominated by the developed markets, the contemporary figures validate the increasingly prominent role of emerging market firms (EMF) in the global economy (Caiazza and Volpe, 2015;Reddy et al, 2022). Cross-border M&As constitute the majority of the foreign direct investments from emerging market nations.…”
Section: Introductionmentioning
confidence: 99%